The Effectiveness of Implementing Art Therapy in Reducing Anxiety Among the Elderly at The Budi Agung Social Welfare Center - Ninef, Violin Irene; Altin Wala, Maria; Aplonia, Marlince; E T Lobho, Kristina (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: The increasing aging population raises concerns about the well-being of the elderly, with anxiety being one of the significant yet often overlooked issues. Art Therapy has been recognized as a promising approach to address anxiety, particularly in the elderly. However, research on the effectiveness of Art Therapy in reducing anxiety among the elderly remains limited, especially at the Budi Agung Social Welfare Center in Kupang. Objective: This study aims to evaluate the effectiveness of implementing Art Therapy in reducing anxiety levels among the elderly at the Budi Agung Social Welfare Center in Kupang. Method: This study employed a quantitative approach with a pre-test post-test control group experimental design. The research population comprised elderly individuals residing at the Budi Agung Social Welfare Center in Kupang. The sampling method utilized was simple random sampling, resulting in a total of 60 elderly participants divided into two groups: the intervention group (receiving Art Therapy) and the control group (without intervention). Data were collected through anxiety questionnaires and observations. Data analysis was conducted using non-parametric statistical tests, such as the Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. Result: The analysis results indicated a significant decrease in anxiety levels within the intervention group following the implementation of Art Therapy (p < 0.05). There was a significant difference observed between the anxiety scores of the intervention group and the control group. Observations also revealed positive changes in the behavior and emotional expression of the elderly participants after undergoing Art Therapy. ConclusionArt Therapy has been proven effective in reducing anxiety among the elderly at the Budi Agung Kupang Social Welfare Center. The practical implication of this finding underscores the importance of integrating art therapy, such as Art Therapy, into elderly health programs to enhance their quality of life and well-being.